'Bourgois Gentilhomme (midden cursus '97/98'. Tweede van links zittend op de grond Adama van Scheltema - Schuitvlot, Nic.,
'Bourgois Gentilhomme (midden cursus '97/98'. Tweede van links zittend op de grond Adama van Scheltema.